Occurrence of Toxic Metals and Metalloids in Muscle and Liver of Italian Heavy Pigs and Potential Health Risk Associated with Dietary Exposure - Ghidini, Sergio; Varra, Maria Olga; Husáková, Lenka; Alborali, Giovanni Loris; Patočka, Jan; Ianieri, Adriana; Zanardi, Emanuela (MDPI, 2022)
Muscle and liver tissues from Italian heavy pigs were analyzed to investigate whether the chronic consumption of these products by local consumers could represent a health risk in relation to the contamination by some toxic metals and metalloids (TMMs). The concentrations of Al, As, Cd, Cr, Cu, Fe, Ni, Pb, Sn, U, and Zn were measured with an inductively coupled plasma-mass spectrometer, while Hg analysis was performed by using a mercury analyzer. Fe, Zn, and Cu were the most abundant elements in both tissues, while U was detected only at ultra-trace levels. As, Cd, Cu, Fe, Hg, Pb, U, and Zn showed significantly higher concentrations in livers compared to muscles (p <= 0.01), with Cd and Cu being 60- and 9-fold more concentrated in the hepatic tissue. Despite this, concentrations of all TMMs were found to be very low in all the samples to the point that the resulting estimated dietary intakes did not suggest any food safety concern. Indeed, intakes were all below the toxicological health-based guidance values or resulted in low margins of exposure. Nevertheless, in the calculation of the worst-case exposure scenario, the children's estimated intake of Cd, Fe, and Zn through the sole consumption of pig liver contributed to more than 23, 38, and 39% of the tolerable weekly intakes of these elements, while the combined consumption of pig liver and pig muscle to more than 24, 46, and 76%. These findings alert about the probability of exceeding the toxicological guidance values of Cd, Fe, and Zn though the whole diet, suggesting long-term negative health effects for the younger population.
Výskyt toxických kovů a metaloidů ve svalech a játrech italských těžkých prasat a potenciální zdravotní riziko spojené s jejich konzumací
Keywords: meat inspection; toxic metals; food safety; toxicity; exposure assessment; chemical risk; těžké kovy; kontaminanty; analýza tkání